Preoperative Correction of Anemia of Chronic Diseases and Application of Bloodless Technology in Mitral and Aortic Valve Replacement - Bogdan N. Gumeniuk (Ukrainian Journal of Cardiovascular Surgery, 2025)
The article is dedicated to the optimization of the treatment of postoperative anemia in patients with mitral and aortic valve replacement through blood saving technology (BST).The aim. To investigate the preoperative combined effect of iron (III) hydroxide and erythropoietin on the level of postoperative anemia after mitral and aortic valve replacement (MAVR) through BST in the conditions of artificial circulation.Material and methods. Preoperative levels of Hb, Ht, iron, and enzymes were studied in 53 patients with com-bined mitral and aortic heart defects. All the patients are divided into groups A, B, C. Patients with normal levels of Hb, Ht, RBC, iron were divided into groups A and B. Patients of group A were operated with the use of donor blood components, and in group B - no donor blood components were used. In group C where the patients had low iron values, preoperative iron correction and erythropoietin stimulation were performed. Operations in group C were performed using BST.Results. According to the study results, the patients of group A needed sufficient volume components of donor blood (621.0 ± 103.0 ml of red cell mass and 713.0 ± 89.0 ml of fresh-frozen plasma) in the operative period. MAVR with BST in group B was possible without transfusion of donor blood preparations, however, Hb decrease by 17.1% dictated the need for preoperative preparation of donor blood components.Correction of low levels of preoperative serum iron in group C resulted in its 8.9-fold rise compared to the pre-operative level, as well as Hb increase by 5.8%. The use of BST during MAVR reduces postoperative anemia by 7.7% and helps to avoid transfusion of donor blood components.Conclusions. Correction of low preoperative levels of iron and erythropoietin in patients with mitral and aortic heart defects reduces the level of postoperative anemia after operations with mitral and aortic valve replacement through BST.